Indian Culture and its Reflection on Advertising: A Perceptual Study of Advertising Practitioners - Swaminathan, Freda; Bansal, Ipshita (Indian Journal of Marketing, 2014)
India’s diverse culture is reflected in the advertising released by top advertisers. This study looked at how advertisers and advertising agency personnel perceived the culture prevalent among Indian consumers, the cultural dimensions of Indian advertising, and its impact on the effectiveness of advertising campaigns. This is a qualitative study conducted amongst senior advertising practitioners from advertising agencies and advertisers. In-depth interviews were conducted to study how the depiction of different stimuli in advertising like celebrity endorsements, humor, language, clothing, religion, patriotism, festivity, and lifestyle influence the culture of consumers. Other aspects like romance, technology, family, friendship, and environment were also studied. Hofstede’s dimensions of culture were used to gain insights on the subject from practitioners. The research identified five waves of change that are transforming the culture of Indian consumers and this is reflected in Indian advertising. These waves have been discussed in detail as waves that bring a change in consumer culture, for a better life, a change to succeed, a change in traditions, a change in the concept of globalization, and a change in the perceptions of value for money. The paper concluded with an assessment of the challenges that advertisers face in dealing with the diverse culture that is prevalent amongst Indian consumers to create effective advertising.